A case of amyotrophic lateral sclerosis which was diagnosed with progressive dysphagia and muscle atrophy. (13th October 2018) - Komata, Tadashi
Abstract: A 79‐year‐old man presented to our outpatient clinic with symptoms of dysphagia, dysarthria, and muscle atrophy of the trunk and upper extremities. These symptoms were gradually progressive, and he had lost substantial weight―20 kg in 2 years. One month later, he was admitted due to dehydration and received tube feeding. The presence of "split hand" suggested amyotrophic lateral sclerosis (ALS). Finally, the patient was diagnosed with ALS by two neurologists. When elderly patients present with progressive dysphagia and muscle atrophy, especially with "split hands, " ALS should be included as a differential diagnosis. Abstract : A 79‐year‐old man, showing dysphagia, dysarthria, and progressive muscle atrophy, was diagnosed with amyotrophic lateral sclerosis (ALS). The "split hand sign" became the clue to suspect ALS. ALS should be included in the differential diagnoses in seeing patients with these signs and symptoms, especially of advanced age.